Developing an active noise control system - Teo, Ying Ying (2015)
As one of the most densely populated cities in the world, noise control has become a pronounced public health concern in Singapore in recent years. At the moment, passive noise control techniques such as building barricades along noise-generating sites are in place to remove or reduce the intensity of the noise reaching people. These barricades are costly but effective to a reduce high frequency noise (Ardekani & Abdullah, 2013) but are ineffective for low frequency noise that humans are more sensitive to. In Chapter 1, we introduce the possibility of using another method – active noise control (ANC) to reduce low frequency noise. The concepts of a single-channel, multichannel ANC system and the relevant concerns of building an ANC system would be presented in Chapter 2. In Chapter 3, there will be a documentation of how the hardware and software ANC system in this project was designed and implemented, as well as the results for the system. Chapter 4 concludes the entire project and offers future research suggestions.